Ventricular repolarization instability quantified by instantaneous frequency of ECG ST intervals - Wan, Xiangkui; Liu, Junjie; Jin, Zhiyao; Zhu, Binru; Zhang, Mingrui (Technology and health care, 2021)
BACKGROUND: Ventricular repolarization instabilities have been documented to be closely linked to arrhythmia development. The electrocardiogram (ECG) ST interval can be used to measure ventricular repolarization. Analyzing the duration variation of the ST intervals can provide new information about the arrhythmogenic vulnerability. OBJECTIVE: In this work, we propose a new method based on mean instantaneous frequency (IF) of the ST intervals to quantitatively evaluate the risk of sudden cardiac deaths (SCDs). METHODS: Two spectral bands, i.e. the low-frequency band (LF, 0–0.15 Hz) and the high-frequency band (HF, 0.15–0.5 Hz), are considered in this paper. Based on IF estimates, the ECG recordings from three MIT-BIH databases that represent different risk levels of SCD occurrence are used, and their mean IFs in the LF and HF bands are calculated. RESULTS: The statistical results show that healthy subjects have a higher mean IF in the HF band and a lower mean IF in the LF band. The experimental results are the opposite for patients with malignant ventricular arrhythmia. CONCLUSION: The proposed mean IF can represent an indirect measure of intrinsic ventricular repolarization instability and can mark cardiac instability associated with SCDs.